Parenting style as a predictor of dietary score change in children from 4 to 14 years of age. Findings from the Longitudinal Study of Australian Children - Burnett, Alissa J; Lamb, Karen E; Spence, Alison C; Lacy, Kathleen E; Worsley, Anthony (My University, 2021)
To examine associations between parenting style and changes in dietary quality score across childhood.
Public Health Nutrition
Keywords: Adolescents; Childhood obesity; Diet quality; Parenting styles; Pre-school children; Health and wellbeing